Preparation method of heat-conducting paste with high heat conductivity

By combining materials such as copolymer epoxy resin, acidified graphite, polyhydroxy resin and liquid metal modified three-dimensional graphene, high thermal conductivity thermal paste is prepared, which solves the problem of thermal paste drying, cracking and powdering and precipitation of silicone oil under high temperature conditions. The problem is that high thermal conductivity and stability are achieved, and the service life and convenience of the equipment are improved.

CN119192860APending Publication Date: 2024-12-27FUJIAN MEITEK THERMAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411566814.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2024-12-27

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides a preparation method of heat-conducting paste with high thermal conductivity, which comprises the following steps: forming a component A by 50-80 parts of copolymer epoxy resin, 10-20 parts of acidified graphite, 3-6 parts of submicron powder and 5-10 parts of a silane coupling agent, and forming a component B by 60-80 parts of polyhydroxy resin, 15-25 parts of liquid metal modified three-dimensional graphene and 8-12 parts of a boron nitride modified aluminate coupling agent; meanwhile, 2-5 parts of a flame retardant and 1-3 parts of a plasticizer are added, so that the heat-conducting paste with good stability and high heat conductivity is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thermal conductive paste, and specifically relates to a method for preparing a thermal conductive paste with high thermal conductivity. Background Art

[0002] Thermal paste (also known as heatsink paste, CPU thermal paste or thermal interface material (TIM)) is a substance used to fill the gap between two surfaces. Its main purpose is to improve the efficiency of heat conduction. In electronic devices, especially in the field of computer hardware, thermal paste is often used between the processor (CPU or GPU) and the heat sink or heat sink to reduce the air gap and enhance the ability of heat to transfer from the processor to the heat dissipation device. Thermal paste is usually made of metal oxides (such as zinc or aluminum oxides), ceramic particles or other thermally conductive fillers mixed with silicone oil.

[0003] Usually, thermal paste is a paste composed of a matrix and a series of new metal oxides, graphite, ceramic materials and other thermal conductive fillers. The thermal conductive network formed between the thermal conductive fillers gives the thermal paste excellent thermal conductivity. According to experience, adding a high amount of powder to the thermal paste can quickly increase the thermal conductivity coefficient, but with the continuous addition of thermal conductive powder, the viscosity of the thermal paste will also increase rapidly, so that the coating, wettability and shape matching of the thermal paste with the interface are reduced, which will lead to an increase in the contact thermal impedance when the thermal paste is used.

[0004] At present, the silicone thermal grease on the market is prone to drying, cracking and powdering during long-term use due to the volatilization and precipitation of low-molecular silicone oil under long-term high temperature conditions, resulting in reduced heat transfer performance and affecting the service life of the equipment. In addition, silicone thermal grease will also precipitate silicone oil during storage, causing inconvenience to the client when using it, and it needs to be stirred before use. Therefore, it is meaningful to develop a preparation method for high thermal conductivity thermal paste. Summary of the invention

[0005] The purpose of the present invention is to provide a high thermal conductivity thermal conductive paste and a preparation method thereof, wherein a component A is formed by using a copolymer epoxy resin, acidified graphite, submicron powder and a silane coupling agent, a component B is formed by using a polyhydroxy resin, liquid metal modified three-dimensional graphene, and boron nitride modified aluminate coupling agent, and a flame retardant and a plasticizer are added at the same time, thereby finally obtaining a high thermal conductivity thermal conductive paste.

[0006] In order to achieve the above object, the present invention provides the following technical solutions: A high thermal conductivity thermal conductive paste comprises the following components in parts by weight: 50-80 parts of copolymer epoxy resin, 10-20 parts of acidified graphite, 3-6 parts of submicron powder, 5-10 parts of silane coupling agent, 60-80 parts of polyhydroxy resin, 15-25 parts of liquid metal modified three-dimensional graphene, 2-5 parts of flame retardant, 8-12 parts of boron nitride modified aluminate coupling agent and 1-3 parts of plasticizer.

[0007] Preferably, the copolymer epoxy resin is prepared using bisphenol F epoxy resin and acrylic block copolymer as raw materials and triphenylphosphine as a catalyst.

[0008] Preferably, the acidified graphite is p-toluenesulfonic acid modified graphite; the submicron powder is a mixture of magnesium oxide-silicon oxide-copper oxide with a particle size of 0.05-1um, wherein the weight ratio of magnesium oxide-silicon oxide-copper oxide is 1:1.2:1-1.5.

[0009] Preferably, the polyhydroxy resin is a double-end hydroxyl-terminated polyethylene; the liquid metal modified three-dimensional graphene is a three-dimensional graphene surface structure modified by liquid metal tin or zinc; the flame retardant is a polyphosphate; the plasticizer is tributyl citrate; and the silane coupling agent is KH560 silane coupling agent.

[0010] A method for preparing a high thermal conductivity thermal conductive paste comprises the following steps: S1: by weight, 80-100 parts of bisphenol F epoxy resin and 20-30 parts of acrylic block copolymer are mixed, 5-7 parts of triphenylphosphine are added, and the mixture is reacted at a temperature of 200-220° C. for 4-6 hours to obtain a copolymer epoxy resin; S2: adding graphite to a 30% by weight aqueous solution of p-toluenesulfonic acid at a solid-liquid ratio of 1 g:25-35 ml, and reacting at a temperature of 100-120° C. for 2-4 hours to obtain acidified graphite; S3: Mix 15-25 parts of liquid metal and 5-8 parts of graphene by weight, and perform ultrasonic treatment at a temperature of 35-45° C. for 35-55 min to obtain liquid metal modified graphene; S4: Take 8-12 parts of boron nitride, 1-3 parts of aluminate coupling agent and 15-25 parts of dimethyl silicone oil by weight, stir and react at a temperature of 120-140° C. for 1-3 hours to obtain a boron nitride modified aluminate coupling agent; S5: Take 50-80 parts of the copolymer epoxy resin described in step S1, 10-20 parts of the acidified graphite described in step S2, 3-6 parts of submicron powder and 5-10 parts of silane coupling agent by weight, stir and react at a temperature of 110-130°C for 1-3h to obtain component A; take 60-80 parts of polyhydroxy resin, 15-25 parts of liquid metal modified three-dimensional graphene, 2-5 parts of flame retardant and 8-12 parts of boron nitride modified aluminate coupling agent, stir and react at a temperature of 120-140°C for 1-3h to obtain component B; mix component A and component B, add 1-3 parts of plasticizer, and ultrasonically treat at a temperature of 70-90°C for 45-75min to obtain a high thermal conductivity thermal conductive paste.

[0011] Preferably, step S1 is specifically as follows: by weight, 85 parts of bisphenol F epoxy resin and 28 parts of acrylic block copolymer are mixed, 6 parts of triphenylphosphine are added at a rate of 3-5 drops / min, and the mixture is reacted at a temperature of 210° C. and a rate of 500 r / min for 5.5 hours to obtain a copolymer epoxy resin.

[0012] Preferably, step S2 is specifically as follows: adding graphite to a 30% by weight aqueous solution of p-toluenesulfonic acid at a solid-liquid ratio of 1 g:33 ml, stirring and reacting at a temperature of 115° C. and a rate of 600 r / min for 2.5 hours to obtain acidified graphite.

[0013] Preferably, step S3 is specifically as follows: by weight, 22 parts of liquid metal and 7 parts of graphene are mixed, and ultrasonic treatment is performed at a temperature of 43° C. and a power of 1500 W for 50 minutes to obtain liquid metal-modified graphene.

[0014] Preferably, step S4 is specifically as follows: by weight, 10 parts of boron nitride, 2 parts of aluminate coupling agent and 22 parts of dimethyl silicone oil are taken, and stirred at a temperature of 125° C. and a speed of 550 r / min for 2.5 hours to obtain a boron nitride modified aluminate coupling agent.

[0015] Preferably, step S5 is specifically as follows: by weight, take 75 parts of the copolymer epoxy resin described in step S1, 16 parts of the acidified graphite described in step S2, 5 parts of submicron powder and 7 parts of silane coupling agent, stir and react at a temperature of 120°C and a rate of 600r / min for 2h to obtain component A; take 75 parts of polyhydroxy resin, 20 parts of liquid metal modified three-dimensional graphene, 3 parts of flame retardant and 10 parts of boron nitride modified aluminate coupling agent, stir and react at a temperature of 135°C and a rate of 450r / min for 2.5h to obtain component B; mix component A and component B, add 2 parts of plasticizer, and ultrasonically treat at a temperature of 85°C and a power of 2500W for 65min to obtain a high thermal conductivity thermal conductive paste.

[0016] Compared with the prior art, the advantages and beneficial effects of the present invention are: 1. The present invention first coats submicron powder with copolymer epoxy resin. Compared with powder of single particle size, the powder is more densely packed and can produce more thermal conductive networks, thus showing more superior thermal conductive performance; under the action of acidified graphite and silane coupling agent, the powder is further cross-linked to form a microscopic cross-linked network.

[0017] 2. The present invention modifies three-dimensional graphene with liquid metal. The three-dimensional graphene cross-linked network can avoid oil separation and liquid metal seepage problems for liquid metal droplets, thereby improving the stability and reliability of the liquid metal composite thermal conductive paste. The aluminate coupling agent is modified with boron nitride, which improves the thermal conductivity while achieving no silicone oil precipitation compared with traditional thermal conductive silicone grease with silicone oil as the matrix.

[0018] 3. The present invention mixes two components A / B with different bases to form a final paste with good storage stability and high thermal conductivity. DETAILED DESCRIPTION

[0019] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] The sources of raw materials used in the present invention are as follows: Bisphenol F epoxy resin comes from Hubei Shiteng Chemical Technology Co., Ltd. with item number 032563; acrylic block copolymer comes from Xi'an Ruixi Biotechnology Co., Ltd. with item number 10324; graphite comes from Shanghai Yuanye Biotechnology Co., Ltd. with item number S26651; aluminate coupling agent comes from Wuhan Kanos Technology Co., Ltd. with item number 03964; dimethyl silicone oil comes from Nanjing Danpei Chemical Co., Ltd. with item number PMX-200; potassium polyphosphate comes from Shandong Jinshengrun Chemical Co., Ltd. with item number 20240710; tributyl citrate comes from Wuhan Jiyesheng Chemical Co., Ltd. with item number A00364.

[0021] Example 1 This embodiment provides a method for preparing a high thermal conductivity thermal conductive paste, comprising the following steps: S1: 80g of bisphenol F epoxy resin and 20g of acrylic block copolymer were mixed, 5g of triphenylphosphine was added at a rate of 3 drops / min, and the mixture was reacted at a temperature of 200°C and a rate of 500r / min for 4h to obtain a copolymer epoxy resin; S2: Add graphite to a 30% by mass aqueous solution of p-toluenesulfonic acid at a solid-liquid ratio of 1g:25ml, and react at a temperature of 100°C and a rate of 600r / min for 2h to obtain acidified graphite; S3: 15 g of liquid metal tin and 5 g of graphene were mixed, and ultrasonic treatment was performed at a temperature of 35°C and a power of 1500 W for 35 min to obtain liquid metal modified graphene; S4: Take 8g of boron nitride, 1g of aluminate coupling agent and 15g of dimethyl silicone oil, stir and react at a temperature of 120°C and a speed of 550r / min for 1h to obtain a boron nitride modified aluminate coupling agent; S5: Take magnesium oxide-silicon oxide-copper oxide submicron powder with a weight ratio of 1:1.2:1 and a particle size of 0.05-1um; take 50g of the copolymer epoxy resin described in step S1, 10g of the acidified graphite described in step S2, 3g of submicron powder and 5g of silane coupling agent KH560, stir and react at a temperature of 110°C and a speed of 600r / min for 1h to obtain component A; take 60g of polyhydroxy resin, 15g of liquid metal tin modified three-dimensional graphene, 2g of potassium polyphosphate and 8g of boron nitride modified aluminate coupling agent, stir and react at a temperature of 120°C and a speed of 450r / min for 1h to obtain component B; mix component A and component B, add 1g of tributyl citrate, and ultrasonically treat at a temperature of 70°C and a power of 2500W for 45min to obtain a high thermal conductivity thermal conductive paste.

[0022] Example 2 This embodiment provides a method for preparing a high thermal conductivity thermal conductive paste, comprising the following steps: S1: 100 g of bisphenol F epoxy resin and 30 g of acrylic block copolymer were mixed, 7 g of triphenylphosphine was added at a rate of 5 drops / min, and the mixture was reacted at a temperature of 220° C. and a rate of 500 r / min for 6 h to obtain a copolymer epoxy resin; S2: Add graphite to a 30% by mass aqueous solution of p-toluenesulfonic acid at a solid-liquid ratio of 1g:35ml, and react at a temperature of 120°C and a rate of 600r / min for 4h to obtain acidified graphite; S3: Mix 25 g of liquid metal tin and 8 g of graphene, and perform ultrasonic treatment at 45°C and 1500 W for 55 min to obtain liquid metal modified graphene; S4: Take 12g of boron nitride, 3g of aluminate coupling agent and 25g of dimethyl silicone oil, stir and react at a temperature of 140°C and a speed of 550r / min for 3h to obtain a boron nitride modified aluminate coupling agent; S5: Take magnesium oxide-silicon oxide-copper oxide submicron powder with a weight ratio of 1:1.2:1.5 and a particle size of 0.05-1um; take 80g of the copolymer epoxy resin described in step S1, 20g of the acidified graphite described in step S2, 6g of submicron powder and 10g of silane coupling agent KH560, stir and react at a temperature of 130°C and a speed of 600r / min for 3h to obtain component A; take 80g of polyhydroxy resin, 25g of liquid metal tin modified three-dimensional graphene, 5g of potassium polyphosphate and 12g of boron nitride modified aluminate coupling agent, stir and react at a temperature of 140°C and a speed of 450r / min for 3h to obtain component B; mix component A and component B, add 3g of tributyl citrate, and ultrasonically treat at a temperature of 90°C and a power of 2500W for 75min to obtain a high thermal conductivity thermal conductive paste.

[0023] Example 3 This embodiment provides a method for preparing a high thermal conductivity thermal conductive paste, comprising the following steps: S1: 85g of bisphenol F epoxy resin and 28g of acrylic block copolymer were mixed, 6g of triphenylphosphine was added at a rate of 4 drops / min, and the mixture was reacted at a temperature of 210°C and a rate of 500r / min for 5.5h to obtain a copolymer epoxy resin; S2: Add graphite to a 30% by mass aqueous solution of p-toluenesulfonic acid at a solid-liquid ratio of 1g:33ml, and react at a temperature of 115°C and a rate of 600r / min for 2.5h to obtain acidified graphite; S3: 22 g of liquid metal tin and 7 g of graphene were mixed, and ultrasonic treatment was performed at a temperature of 43°C and a power of 1500 W for 50 min to obtain liquid metal modified graphene; S4: Take 10g of boron nitride, 2g of aluminate coupling agent and 22g of dimethyl silicone oil, stir and react at a temperature of 125°C and a speed of 550r / min for 2.5h to obtain a boron nitride modified aluminate coupling agent; S5: Take magnesium oxide-silicon oxide-copper oxide submicron powder with a weight ratio of 1:1.2:1.4 and a particle size of 0.05-1um; take 75g of the copolymer epoxy resin described in step S1, 16g of the acidified graphite described in step S2, 5g of submicron powder and 7g of silane coupling agent KH560, stir and react at a temperature of 120°C and a speed of 600r / min for 2h to obtain component A; take 75g of polyhydroxy resin, 20g of liquid metal tin modified three-dimensional graphene, 3g of potassium polyphosphate and 10g of boron nitride modified aluminate coupling agent, stir and react at a temperature of 135°C and a speed of 450r / min for 2.5h to obtain component B; mix component A and component B, add 2g of tributyl citrate, and ultrasonically treat at a temperature of 85°C and a power of 2500W for 65min to obtain a high thermal conductivity thermal conductive paste.

[0024] Comparative Example 1 The difference between this comparative example and Example 1 is that step S1 is omitted, and commercially available common epoxy resin (manufacturer, model) is directly used in step S5, and the other steps are the same.

[0025] Comparative Example 2 The difference between this comparative example and Example 1 is that step S2 is missing, and the other steps are the same.

[0026] Comparative Example 3 The difference between this comparative example and Example 1 is that step S3 is missing, and the other steps are the same.

[0027] Comparative Example 4 The difference between this comparative example and Example 1 is that step S4 is missing, and the other steps are the same.

[0028] Comparative Example 5 The difference between this comparative example and Example 1 is that no submicron powder is added in step S5, and the other steps are the same.

[0029] Comparative Example 6 The difference between this comparative example and Example 1 is that no plasticizer is added in step S5, and the other steps are the same.

[0030] Performance Testing: Thermal conductivity: A thermal conductivity meter with model Hot Disk TPS2500S was used to measure the thermal conductivity of the thermal paste using the transient plane heat source method in accordance with the international standard ISO 22007-2 Determination of thermal conductivity and thermal diffusivity of plastics. Three parallel samples were measured in each group and the average value was taken. Viscosity: The viscosity of the thermal paste was measured using a rheometer, using parallel plates with a diameter of 25 mm, a gap of 200 μm and a shear rate of 1.0 (1 / s).

[0031] The results are shown in the table below: Table 1 Performance test results

[0032] It can be seen from the above performance test results that the high thermal conductivity and low viscosity of Examples 1-3 are effective. In particular, the comprehensive performance of Example 3 is the most outstanding. However, since the comparative example does not adopt the necessary technical solution, it is significantly worse than the example in the corresponding performance test. The above experimental results further prove the importance of the technical solution defined in the present invention for its technical effect.

[0033] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A high thermal conductivity thermal conductive paste, characterized in that: The invention comprises the following components in parts by weight: 50-80 parts of copolymer epoxy resin, 10-20 parts of acidified graphite, 3-6 parts of submicron powder, 5-10 parts of silane coupling agent, 60-80 parts of polyhydroxy resin, 15-25 parts of liquid metal modified three-dimensional graphene, 2-5 parts of flame retardant, 8-12 parts of boron nitride modified aluminate coupling agent and 1-3 parts of plasticizer.

2. A high thermal conductivity thermal conductive paste according to claim 1, characterized in that: The copolymer epoxy resin is prepared by taking bisphenol F epoxy resin and acrylic acid block copolymer as raw materials and triphenylphosphine as catalyst.

3. The high thermal conductivity thermal conductive paste according to claim 1, characterized in that: The acidified graphite is p-toluenesulfonic acid modified graphite; the submicron powder is a mixture of magnesium oxide-silicon oxide-copper oxide with a particle size of 0.05-1um, wherein the weight ratio of magnesium oxide-silicon oxide-copper oxide is 1:1.2:1-1.

5.

4. The high thermal conductivity thermal conductive paste according to claim 1, characterized in that: The polyhydroxy resin is double-terminated hydroxyl-terminated polyethylene; the liquid metal modified three-dimensional graphene is a three-dimensional graphene surface structure modified by liquid metal tin or zinc; the flame retardant is polyphosphate; the plasticizer is tributyl citrate; and the silane coupling agent is KH560 silane coupling agent.

5. A method for preparing a high thermal conductivity thermal conductive paste, characterized in that: The steps include: S1: by weight, 80-100 parts of bisphenol F epoxy resin and 20-30 parts of acrylic block copolymer are mixed, 5-7 parts of triphenylphosphine are added, and the mixture is reacted at a temperature of 200-220° C. for 4-6 hours to obtain a copolymer epoxy resin; S2: adding graphite to a 30% by weight aqueous solution of p-toluenesulfonic acid at a solid-liquid ratio of 1 g:25-35 ml, and reacting at a temperature of 100-120° C. for 2-4 hours to obtain acidified graphite; S3: Mix 15-25 parts of liquid metal and 5-8 parts of graphene by weight, and perform ultrasonic treatment at a temperature of 35-45° C. for 35-55 min to obtain liquid metal modified graphene; S4: Take 8-12 parts of boron nitride, 1-3 parts of aluminate coupling agent and 15-25 parts of dimethyl silicone oil by weight, stir and react at a temperature of 120-140° C. for 1-3 hours to obtain a boron nitride modified aluminate coupling agent; S5: Take 50-80 parts of the copolymer epoxy resin described in step S1, 10-20 parts of the acidified graphite described in step S2, 3-6 parts of submicron powder and 5-10 parts of silane coupling agent by weight, stir and react at a temperature of 110-130°C for 1-3h to obtain component A; take 60-80 parts of polyhydroxy resin, 15-25 parts of liquid metal modified three-dimensional graphene, 2-5 parts of flame retardant and 8-12 parts of boron nitride modified aluminate coupling agent, stir and react at a temperature of 120-140°C for 1-3h to obtain component B; mix component A and component B, add 1-3 parts of plasticizer, and ultrasonically treat at a temperature of 70-90°C for 45-75min to obtain a high thermal conductivity thermal conductive paste.

6. The method for preparing a high thermal conductivity thermal conductive paste according to claim 5, characterized in that: Step S1 is specifically as follows: by weight, 85 parts of bisphenol F epoxy resin and 28 parts of acrylic block copolymer are mixed, 6 parts of triphenylphosphine is added at a rate of 3-5 drops / min, and the mixture is reacted at a temperature of 210° C. and a rate of 500 r / min for 5.5 hours to obtain a copolymer epoxy resin.

7. The method for preparing a high thermal conductivity thermal conductive paste according to claim 5, characterized in that: Step S2 is specifically as follows: adding graphite to a 30% by weight aqueous solution of p-toluenesulfonic acid at a solid-liquid ratio of 1 g:33 ml, stirring and reacting at a temperature of 115° C. and a speed of 600 r / min for 2.5 hours to obtain acidified graphite.

8. The method for preparing a high thermal conductivity thermal conductive paste according to claim 5, characterized in that: Step S3 is specifically as follows: by weight, 22 parts of liquid metal and 7 parts of graphene are mixed, and ultrasonic treatment is performed at a temperature of 43° C. and a power of 1500 W for 50 minutes to obtain liquid metal-modified graphene.

9. The method for preparing a high thermal conductivity thermal conductive paste according to claim 5, characterized in that: Step S4 is specifically as follows: in parts by weight, 10 parts of boron nitride, 2 parts of aluminate coupling agent and 22 parts of dimethyl silicone oil are taken, and stirred at a temperature of 125° C. and a speed of 550 r / min for 2.5 hours to obtain a boron nitride modified aluminate coupling agent.

10. The method for preparing a high thermal conductivity thermal conductive paste according to claim 5, characterized in that: Step S5 is specifically as follows: by weight, take 75 parts of the copolymer epoxy resin described in step S1, 16 parts of the acidified graphite described in step S2, 5 parts of submicron powder and 7 parts of silane coupling agent, stir and react at a temperature of 120°C and a rate of 600r / min for 2h to obtain component A; take 75 parts of polyhydroxy resin, 20 parts of liquid metal modified three-dimensional graphene, 3 parts of flame retardant and 10 parts of boron nitride modified aluminate coupling agent, stir and react at a temperature of 135°C and a rate of 450r / min for 2.5h to obtain component B; mix component A and component B, add 2 parts of plasticizer, and ultrasonically treat at a temperature of 85°C and a power of 2500W for 65min to obtain a high thermal conductivity thermal conductive paste.